Re-reading Ishi's story - Denzin, Norman K., author.
1 online resource (x, 122 pages)
Keywords: "This book is the fifth in the series by Norman K. Denzin - a sweeping, critical examination of representation of Native Americans and NA culture in art, film, television and popular culture. Using his well-recognized mix of dramatization, incisive cultural critique and sensitive reframing, Denzin recasts the story of the man dubbed 'Ishi' by Alfred Kroeber to examine the huge injustices perpetrated upon Native Californians, and how subsequent performance and interpretation reduced their stories - and Ishi's - to show and pantomime, hiding the true nature of the treatment of Native Americans. Suitable for scholars and students of qualitative inquiry, anthropology and Native American Studies"--